The role of anti-Müllerian hormone in the pathogenesis and pathophysiological characteristics of polycystic ovary syndrome. (April 2016) - Qi, Xinyu; Pang, Yanli; Qiao, Jie
Abstract: Polycystic ovarian syndrome (PCOS) is one of the major causes of anovulatory infertility. High levels of anti-Müllerian hormone (AMH) in the serum of PCOS patients participate in the major steps of the anovulation, and are related to pathogenesis and pathophysiological characteristic of PCOS, including the interactions of AMH with intra/extra ovarian factors like FSH, LH, androgen, and estrogen, as well as the role of AMH in folliculogenesis of PCOS. AMH promotes follicular atresia which may participate in the follicle pattern in PCOS patients. Recent years, the abnormally increased AMH in serum and follicle fluid of PCOS patients have attracted many scholars' attention. In this review, we summarized the role of AMH played in PCOS patients. It is of great significance for clarifying the role of AMH in the diagnosis and treatment of PCOS patients because AMH has the potential to increase our understanding of ovarian pathophysiology and to guide the clinical management of a broader range of conditions.